A newly recognised species that has been confused with the global polyphagous pest scale insect, Coccus hesperidum Linnaeus (Hemiptera: Coccomorpha: Coccidae) - Lin, Yen-Po; Tanaka, Hirotaka; Cook, Lyn G. (Zootaxa, 2017)
Coccus hesperidum L. (Hemiptera: Coccomorpha: Coccidae), the type species of the soft scale genus Coccus L., the family Coccidae and the whole of the scale insects (Coccoidea), is a cosmopolitan plant pest. Using DNA sequence data and morphological comparisons, we determine that there is a distinct species that is morphologically very similar to C. hesperidum. Here, we describe the species as Coccus praetermissus Lin & Tanaka sp. n., based on adult female specimens from Australia, Malaysia and Thailand. The adult female of C. praetermissus sp. n. differs from C. hesperidum in having dorsal setae with bluntly rounded tips, whereas they are sharply pointed in C. hesperidum. A detailed description of the newly recognised species is provided, incorporating adult female morphology and DNA sequences from mitochondrial and nuclear loci. Our examination of slides from The Natural History Museum, London, and several Australian institutions indicates that C. praetermissus sp. n. has been confused sometimes with C. hesperidum s. s. These findings have potential relevance to plant biosecurity and quarantine because C. hesperidum is cosmopolitan whereas C. praetermissus sp. n., which is also polyphagous and the two species can share many host plants, currently appears to be more geographically restricted. Additionally, there is deep genetic divergence within C. praetermissus sp. n. that might indicate that it is a cryptic species complex, but wider geographic sampling is required to test this possibility.